Childlessness, Childfreeness and Compensation - Marie-Louise Leroux; Pierre Pestieau; Grégory Ponthiere (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study the design of a fair family policy in an economy where parenthood is regarded either as desirable or as undesirable, and where there is imperfect fertility control, leading to involuntary childlessness/parenthood. Using an equivalent consumption approach in the consumption-fertility space, we first show that the identification of the worst-off individuals is not robust to how the social evaluator fixes the reference fertility level. Adopting the ex post egalitarian social criterion, which gives priority to the worst off in realized terms, we then examine the compensation for involuntary childlessness/parenthood. Unlike real-world family policies, a fair family policy does not always involve positive family allowances to (voluntary) parents, and may also, under some reference fertility levels, involve positive childlessness allowances. Our results are robust to assuming asymmetric information and to introducing Assisted Reproductive Technologies.
Keywords: J13; I38; 330; fertility; childlessness; family policy; compensation fairness